Strategi Perang Menurut Hukum Humaniter Internasional: Legalkah Metode Blokade? - Jazirah, Hardinna Putri; Tuhulele, Popi; Riry, Welly Angela (Uti Possidetis: Journal of International Law, 2022)
This article discusses the legality of using the blockade method in armed conflict and its legal implications as a war strategy according to International Humanitarian Law. The purpose of this paper is to find out how the use of blockades of a legal nature and its implementation in accordance with Humanitarian Law.Â  As a method of war, blockade is often used in armed conflict to be a method that is not in accordance with international law sources because it can cause losses and casualties. In fact, there are many regulations governing the blockade including the Declaration of Paris 1856 which explains the effectiveness of the blockade, the Declaration of London 1909 which regulates the guarantee of the rights of neutral countries, the 1949 Geneva Conventions which also regulates provisions regarding the delivery of humanitarian aid during the blockade in conflict areas, the 1994 San Remo Manual which regulates the legal conditions for applying the blockade. In addition, this regulation is also often used by legal experts to express their opinions regarding the blockade so that it becomes the primary reference source for judges to find the law. Therefore, to complete the blockade provisions, the role of international organizations is needed to provide supervision, provide strict sanctions and the importance of state party commitments in implementing the blockade method.